The Targeted Killings Judgment: a preliminary assessment - Schondorf, Roy S. (Journal of international criminal justice, 2010)
This judgment is one of the most important contributions in recent years by a national court to the development of the laws governing armed conflicts between states and non-state actors taking place outside of the territory of the state involved. However, some contentious issues should not be passed over in silence. The Israeli Court applied the laws of international armed conflict to any case of armed conflict that crosses borders of the state even if the conflict does not involve belligerent occupation, without, however, providing any authority or explanation for this expansion of the class of international armed conflict. Furthermore, the Court rejected the Government's argument that a third category of unlawful combatants exists under international law, but its analysis on the issue does not enable the reader to fully understand the substantive considerations leading to the Court's conclusion. Although the Court's reference to academic literature is welcome, it cannot replace an assessment of the sources and rules of international law. Finally, the Court set out various requirements restricting the Israeli government's attacks on terrorists taking direct part in hostilities. These requirements, however, go beyond what is commonly considered to be mandated under the laws of international armed conflict: it is difficult to find support for them in state practice or in less recent academic literature interpreting that body of law